Murder, Manslaughter, or Justified Retribution? Tom Williams, Mi’kmaw Law, and Colonial Justice on Prince Edward Island, 1839 - Jarvis, Anna K.G. (Acadiensis, 2022)
In 1839, in the British North American colony of Prince Edward Island, Tom Williams, a Mi’kmaw man, was convicted of murdering another Mi’kmaw man, Joe Louis, and sentenced to hang. Williams, however, did not hang. This article suggests possible reasons the colonial government chose to commute Williams’s sentence, linking the case to the dispossession of the Mi’kmaq and their subsequent marginalization by settler society as well as the “land question” then dominating the Island. The case epitomizes the ascendancy of British colonial law and the concurrent weakening of Mi’kmaw law in the colony.